Millennials Intention To Purchase Online Travel Agent Products: Moderation Analysis - Syarief Darmoyo; Rakhdiny Sustaningrum (Jurnal Manajemen, 2022)
As technology develops, service users who utilize technology have increased along with the emergence of mobile phone application-based services such as social media, online games, and entertainment. However, technological developments are different from growth in the service sector. The RI service sector's productivity is relatively lower than other countries in ASEAN, where Indonesia is still struggling in the traditional service sector such as construction and trade. Digital marketing is one of the disruptive changes that significantly affect the image of a product. So the need for research on how effective strategies for the service sector are specifically for millennials. The purpose of this study was to determine the effect of social media and eWOM on millennial intentions to purchase online travel agent products and to analyze whether firm reputation moderates the influence of social media and eWOM on millennial intentions to purchase online travel agent products. Data collection was carried out using Google form on 270 millennials in Jabodetabek. Hierarchical regression analysis shows that social media and eWOM influence millennial intentions to purchase online travel agent products. Beside, firm reputation only moderates the influence of social media and eWOM on millennial intentions to purchase online travel agent products.